PENERAPAN DIGITAL GOVERNMENT DALAM UPAYA MENINGKATKAN PELAYANAN MASYARAKAT MELALUI APLIKASI SIPADU DANGIN PURI KANGIN DI KOTA DENPASAR - Ricky, Dwipayana; Supriliyani, Ni Wayan; Wirantari, I Dewa Ayu Putri (CITIZEN CHARTER, 2024)
Dangin Puri Kangin Village was named a digital village and smart village. The latest innovation presented by Dangin Puri Kangin Village is the SIPADU Dangin Puri Kangin Application as an effort to improve services to the community. In its implementation, several problems were found, such as a small number of application users, a lack of socialization, a lack of application performance, and a lack of quality human resources. This research aims to determine the application of digital government in an effort to improve community services through the SIPADU Dangin Puri Kangin Application in Denpasar City. The problem study uses Jungwoo Lee's digital government dimension indicators, consisting of data integration, adopting technology, service orientation, people and governance. The research method used is qualitative with a descriptive approach. Data was collected through interviews, observation and documentation studies. The research results show that the implementation of digital government through the SIPADU Dangin Puri Kangin Application has gone quite well but has not yet run optimally. There are several obstacles such as application data not being connected, system errors, people not being familiar with the use of technology, lack of application operators, lack of transparency regarding specific application performance, and socialization that has not been optimal. Recommendations that can be given are connecting application data, improving the quality and developing application service features, realizing an increase in the number of application operators, maximizing socialization.   Keywords: Digital Government, Service To The Community, SIPADU Dangin Puri Kangin Application.